1982
DOI: 10.1080/14640748208400884
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Conditioning Resulting from a Reduction in the Magnitude of Reinforcement

Abstract: Five experiments, all employing conditioned suppression in rats, studied inhibitory conditioning to a stimulus signalling a reduction in shock intensity. Experimental subjects were conditioned to a tone signalling a 1.0 mA shock and to a tone-light compound signalling a 0.4 mA shock. On a summation test in which it alleviated the suppression maintained by a third stimulus also associated with the 1-0 mA shock, the light was established as a conditioned inhibitor. Retardation tests gave ambiguous results : the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 15 publications
2
29
0
Order By: Relevance
“…Holland and Gallagher (1993b) found that rats acquired substantial excitatory learning about the added auditory CS, supporting models like Pearce and Hall's (1980). Although some investigations using downshift procedures have revealed inhibitory learning (e.g., Cotton, Goodall, & Mackintosh, 1982;Holland, 1988, Wagner, Mazur, Donegan, & Pfautz, 1980, the frequent observation of substantial excitatory learning (e.g., Bucci, Holland, & Gallagher, 1998;Dickinson, et al, 1976;Dickinson & Mackintosh, 1979;Holland, 1984Holland, , 1988Holland & Gallagher, 1993b) has been a major source of support for the claim that the disconfirmation of reinforcement expectancies can enhance processing of CSs. Indeed, as we discuss later in this article, we have used excitatory learning in unblocking as a tool for investigating brain mechanisms involved in attentional processes such as those specified in the Pearce-Hall (1980) model (Bucci, et al, 1998;Holland & Gallagher, 1993b.…”
mentioning
confidence: 88%
“…Holland and Gallagher (1993b) found that rats acquired substantial excitatory learning about the added auditory CS, supporting models like Pearce and Hall's (1980). Although some investigations using downshift procedures have revealed inhibitory learning (e.g., Cotton, Goodall, & Mackintosh, 1982;Holland, 1988, Wagner, Mazur, Donegan, & Pfautz, 1980, the frequent observation of substantial excitatory learning (e.g., Bucci, Holland, & Gallagher, 1998;Dickinson, et al, 1976;Dickinson & Mackintosh, 1979;Holland, 1984Holland, , 1988Holland & Gallagher, 1993b) has been a major source of support for the claim that the disconfirmation of reinforcement expectancies can enhance processing of CSs. Indeed, as we discuss later in this article, we have used excitatory learning in unblocking as a tool for investigating brain mechanisms involved in attentional processes such as those specified in the Pearce-Hall (1980) model (Bucci, et al, 1998;Holland & Gallagher, 1993b.…”
mentioning
confidence: 88%
“…Conversely, at time 0 (US2-Same and US 1 coincident), the inhibitory powers of US2-Same omission outweigh its excitatory influences on CS-US 1 association, and the added CS would become a net inhibitor. It is worth noting that the published instances of downshifts in reinforcer magnitude that produced inhibition (e.g., Cotton, et al, 1982;Mackintosh & Cotton, 1985;Wagner et al 1980) all contrasted a large single US with a smaller single US-that is, presented the downshift at time 0,-and most published instances of excitatory conditioning with downshifts involved the omission of another, subsequent event-that is, one presented at time X. By similar logic, if increasing the salience of US2, by making it different from US1, shifts those gradients to the right (dotted curves), then the omission of a more salient US2-Diff may generate net inhibition over longer US1-US2 intervals than with omission of US-Same.…”
Section: Methodsmentioning
confidence: 99%
“…Some changes establish inhibition to the added cue. For example, whereas Dickinson, Hall, and Mackintosh (1976) found that a reduction in the number of shocks delivered resulted in excitatory conditioning, Wagner, Mazur, Donegan, and Pfautz (1980) and Cotton, Goodall, and Mackintosh (1982) found that a reduction in the intensity of a single shock established inhibition to the added cue. Similarly, Mackintosh and Cotton (1985) found that a reduction in the concentration of a sucrose solution US produced inhibitory conditioning of the added cue.…”
mentioning
confidence: 99%
“…We can justify this claim by returning to the demonstration by Cotton et al (1982) showing that conditioned inhibition can be obtained by simply reducing the magnitude of the reinforcer delivered when A and B were presented together (A+ AB+). A tone (playing the role of A) was accompanied by a 1ma shock, and a tone/light compound (AB) was followed by a 0.4 mA shock.…”
Section: What Is Learned During Inhibitory Conditioning?mentioning
confidence: 99%
“…The reduction in the reinforcement (or in the probability of reinforcement) is itself enough to confer inhibitory properties on B (Cotton, Goodall and Mackintosh, 1982;Harris, Kwok and Andrew, 2014). These studies, and others like them, suggest that what is crucial in developing conditioned inhibition is that an expectation of one level or rate of reinforcement is contradicted by experience, and that this leads to the development of something quite different to simple excitatory learning.…”
Section: Acquisitionmentioning
confidence: 99%